The exploration and exploitation of shale gas in Algeria: Surveying key developments in the context of climate uncertainty. (September 2022) - Boudalia, Sofiane; Okoth, Sheila A.; Zebsa, Rabah
Highlights: Shale gas exploitation can increase climate change effects in Algeria. Climate change can exacerbate hydraulic fracturing effects on the environment and human health. Key lessons should be drawn from shale gas experiences in producing countries. Algerian energy and environmental policy should be adapted to current knowledge. Shale gas pricing should consider the costs of environmental and human health impacts. Abstract: Algeria ratified the 2015 Paris Agreement on Climate Change which is committed to reduce greenhouse gas emissions through renewable energy promotion, expanding forest areas and improving water resources. However, the exploration and the exploitation of shale gas are authorized in Algeria. Here, we discuss the socioeconomic factors that have led Algeria to authorize shale gas exploitation regardless of the potential effects of hydraulic fracturing on biodiversity loss and human health under climate change uncertainty context. Data reported show the difficulty to understand the multifaceted aspect of shale gas impacts. Indeed, without a comprehensive environmental assessment (air, soil, water and biodiversity) and human health impacts under climate change context, there is no clear evidence regarding the real costs, on the one hand, and the palpable benefits, on the other, of shale gas exploitation. Scientific data actualization and fully recognizing evidence in the literature are recommended when evaluating the potential adverse effects of unconventional gas on human and animal health, and also when creating hydraulic fracturing legislation. The development of alternative ecofriendly tools and methods to fossil energy sources (e.g., solar photovoltaics, wind, and geothermal energy) has become an emergency to help diversify the economy and safeguard natural resources for future generations. Graphical abstract: Image, graphical abstract